Towards a common vision of climate, peace, security and migration in Mozambique - Maviza, Gracsious; Caroli, Giulia; Makanda, Joseph; Tarusarira, Joram; Sax, Niklas; Gadu, Siyaxola; Synnestvedt, Thea; Mandlenkosi, Maphosa; De Coning, Cedric; Savelli, Adam; Basel, Ashleigh; Carneiro, Bia; et al. (2024)
Mozambique faces significant challenges due to its vulnerability to climate variability and change, exacerbated by geographical factors and historical conflicts. In Mozambique, climate change manifests in the form of extreme weather events, such as droughts and cyclone-related flooding. These events have caused displacement, and contributed to food and water insecurity, which in turn have increased pressure on livelihoods and related social tensions. In some regions, such as Cabo Delgado, these developments, in combination with other factors, have resulted in significant insecurity and displacement. The compounding effects of climate change, instability and under-development will have an impact on Mozambique’s ability to achieve the sustainable development goals. Recognizing the intricate interplay between climate change, displacement, fragility, and conflict is crucial for developing durable solutions and enhancing the resilience of most affected communities.